1978
DOI: 10.1111/j.1476-5381.1978.tb07009.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHOLIPASE A2 ACTIVITY OF GUINEA‐PIG ISOLATED PERFUSED LUNGS: STIMULATION, AND INHIBITION BY ANTI‐INFLAMMATORY STEROIDS

Abstract: 1 A simple double-isotope assay for phospholipase A2 activity of perfused organs is described. 2 Guinea-pig lungs perfused through the pulmonary circulation exhibit a low background enzyme activity. This activity is blocked by dexamethasone, betamethasone and hydrocortisone, mepacrine, procaine or chlorpromazine. Aspirin and indomethacin are without effect. 3 Mechanical trauma, antigen challenge or injections of bradykinin, rabbit aorta contracting substance-releasing factor (RCS-RF) or histamine increase 'bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(82 citation statements)
references
References 26 publications
5
76
0
Order By: Relevance
“…Whether inhibition by glucocorticoids of prostaglandin synthesis elicited by NA and All but not by AVP, Bk or A-23187 reflects a difference in phospholipase species activated by these agents in the rat kidney is not known. Blackwell et al (1978) and Robinson & Hoult (1980) have reported that glucocorticoids also failed to alter the effect of Bk but not that of other agents such as histamine or antigen challenge in enhancing prostaglandin synthesis in the guinea-pig perfused lung, and they attributed this differential effect of glucocorticoids to two distinct 'types' or 'pools' of phospholipase. However, Zusman & Keiser (1980) have shown that in renomedullary interstitial cells, dexamethasone inhibited prostaglandin synthesis elicited by Bk as well as All and AVP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether inhibition by glucocorticoids of prostaglandin synthesis elicited by NA and All but not by AVP, Bk or A-23187 reflects a difference in phospholipase species activated by these agents in the rat kidney is not known. Blackwell et al (1978) and Robinson & Hoult (1980) have reported that glucocorticoids also failed to alter the effect of Bk but not that of other agents such as histamine or antigen challenge in enhancing prostaglandin synthesis in the guinea-pig perfused lung, and they attributed this differential effect of glucocorticoids to two distinct 'types' or 'pools' of phospholipase. However, Zusman & Keiser (1980) have shown that in renomedullary interstitial cells, dexamethasone inhibited prostaglandin synthesis elicited by Bk as well as All and AVP.…”
Section: Discussionmentioning
confidence: 99%
“…These observations together with our findings suggest that the effect of glucocorticoids on prostaglandin synthesis may also vary in different cell types and tissues. Whether these differences are related to their ability to stimulate the synthesis of phospholipase A2 inhibitor (Flower & Blackwell, 1979;Hirata et al, 1980;Cloix et al, 1983) or to differences in sensitivity of various hypothetical phospholipase A2 'pools' (Blackwell et al, 1978;Robinson & Hoult, 1980;Schwartzman et al, 1981) and/or alterations in the interaction of agonists with their receptor sites during treatment with glucocorticoids remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is specific for the glucocorticoids (Hong & Levine, 1976;Nijkamp etal., 1976;Tam etal., 1977;Blackwell et al, 1978;Flower & Blackwell, 1979;Di Rosa & Persico, 1979;Carnuccio et al, 1980;Hirata etal., 1980;Blackwell et al, 1980;Hirata etal., 1981), and depends upon receptor occupation as well as transcriptional and translational events within the target cells (Danon & Assouline, 1978;Russo-Marie, Paing & Duval, 1979;Flower & Blackwell, 1979;Di Rosa & Persico, 1979;Carnuccio et al, 1980;Hirata etal., 0007-1188/82/050185-10 $01.00 1980; Blackwell etal., 1980;Hirataetal., 1981). The anti-inflammatory effect of glucocorticoids in the rat is also dependent on such a chain of events (Tsurufuji, Sugio & Takemasa, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…These results therefore suggest decreased functioning of the ~-adrenoceptors or altered functioning of mechanisms mediating the biological activity. Nijkamp et al (1976) and Blackwell et al (1978) suggested that several agents such as antigen, histamine and RCS-RF that release prostaglandin endoperoxides and thromboxane A2 from guinea pig perfused lungs probably do so by liberating the substrate from intracellular lipid stores through activation of phospholipase A2. H. influenzaevaccinated lungs released more prostaglandins and thromboxanes following antigen challenge and stimulation of phospholipase A2 is one of the possible explanations.…”
Section: Discussionmentioning
confidence: 99%